Transfer of Vesicles From Schwann Cells to Axons: a Novel Mechanism of Communication in the Peripheral Nervous System - Lopez-Verrilli, María Alejandra; Court, Felipe A. (Frontiers in Physiology, 2012)
Schwann cells (SCs) are the glial component of the peripheral nervous system, with essential roles during development and maintenance of axons, as well as during regenerative processes after nerve injury. SCs increase conduction velocities by myelinating axons, regulate synaptic activity at presynaptic nerve terminals and are a source of trophic factors to neurons. Thus, development and maintenance of peripheral nerves are crucially dependent on local signaling between SCs and axons. In addition to the classic mechanisms of intercellular signaling, the possibility of communication through secreted vesicles has been poorly explored to date. Interesting recent findings suggest the occurrence of lateral transfer mediated by vesicles from glial cells to axons that could have important roles in axonal growth and axonal regeneration. Here, we review the role of vesicular transfer from SCs to axons and propose the advantages of this means in supporting neuronal and axonal maintenance and regeneration after nerve damage.